Efektivitas Teknik Storytelling Menggunakan Media Wayang Topeng Malang untuk Meningkatkan Karakter Fairness Siswa Sekolah Dasar - Krisphianti, Yuanita Dwi; Hidayah, Nur; Irtadji, Moh. (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This study aims to determine the effectiveness of storytelling technique using Malang mask puppets media to enhance the fairness of elementary school studentsâ character. The research design is true experiment with pretest-posttest one-group designs. The subject of research was ten students of grade VI Elementary School in Malang determined through the random assignment technique. Data collection instruments used questionnaires of character fairness and observation guidelines. Data analysis technique was used to test the effectiveness of the Storytelling technique using Wilcoxon test. The results of data analysis shows significant value (sig) 0.005> 0.05, which means that the hypothesis is accepted. So we can conclude that storytelling technique using a Malang mask media can improve effectively the character of fairness of grade VI elementary school students. The results of this study is useful for elementary school teachers and guidance and counseling teachers as an alternative to an effective technique to develop character fairness of elementary school students.